Changes of the gait induced by two different conservative methods applied to correct flexible flat feet in children 5 to 9 years old: foot orthoses vs foot orthoses supplemented with Zukunft-Huber manual therapy - Boryczka-Trefler Anna; Kalinowska Małgorzata; Szczerbik Ewa; Stępowska Jolanta; Łukaszewska Anna; Syczewska Małgorzata (Sciendo, 2023)
Study aim: A flexible flat foot (FFF), one of the most common postural deformities among children, should not be perceived as an isolated problem of static alignment of foot and ankle, but as a part of dynamic biomechanical chain of a lower extremity, pelvis, and lower back. The aim of the study was to compare the impact of two methods, used for treating FFF, on the gait pattern in children after 12 months treatment.